How Confident are EFL Prospective Teachers toward Technology? - Fika Megawati; Fitria Nur Hasanah; Choirun Nisak Aulina; Mauliya Avivi; Nur Sholikha Muntiari (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2020)
The advance of ICT development in educational context encourages educators to increase their competence towards technology integration for classroom activities. Consequently, this phenomenon affects teacher education program to equip student teachers as the digital natives in this fourth industrial revolution era with skills accommodating their technology literacy as well as practice. However, to determine the appropriate integration model and supporting training program, analyzing technology confidence seems to be an important thing for initial development step for an institution. This study aims to investigate technology competence of English prospective teachers in terms of applications use capability, technology confidence based on GPA, and TPACK confidence. Questionnaire was used as the instrument, and it was administered to twenty eight participants. The data was analyzed descriptively. The findings reveal that most of the subjects are familiar with the technology application. Further, not all of the subjects are confident to their ICT competence. Inserting GPA information to the prospective teachers’ profile, it shows that high GPA do not guarantee high confidence on ICT use. For TPACK confidence result, it shows that more than 45% are confident to integrate technology in their classroom instruction.